Effect of Carbon Fiber on Microwave Deicing Efficiency of Pavement Concrete. Issue 3 (April 2021) - Meng, Xin; Bai, Erlei; Xia, Wei; Huang, Zhe; Wang, Zhihang
Abstract: Snow and icing on roads in winter will bring serious consequences to traffic safety. Microwave deicing, as a new type of environmentally friendly road surface deicing method, has the characteristics of environmental protection, pollution-free, and high ice removal rate, but its low deicing efficiency limits its use. Carbon fiber has good electrical and thermal conductivity, wear resistance, etc., and can provide a new composite material for road surface deicing. Taking carbon fiber concrete as the research object, the effect of different carbon fiber length on the microwave heat absorption efficiency of concrete is studied. The results found that: as the length of carbon fiber increases, the temperature rise at the same time increases exponentially, the higher the efficiency of carbon fiber concrete for absorbing and heating.